Study of Immuno-physiological Alterations Induced by Helicobacter Pylori Infection Among Population in El-Baida City, Libya - Marfoua Ali; Nagla Bait Almal; Manal Mohammed (AlQalam Journal of Medical and Applied Sciences, 2021)
Background. This work was carried out to investigate the changes in hematological and some physiological parameters among patients with H. pylori Admitted in El-Beida City, Libya. Methods. This study was carried out in 11 consecutive months (Oct 2018 to Aug 2019). A total of 181 adult patients were divided into two groups upon presence and absent of antibodies against to H. pylori. The positive group had 34 (60.7%) males, 102 (81.6%) females and the negative group had 22 (39.3%) males and 23 (18.4%) females. Results. Highest prevalence with positive H. pylori infection was noted in age group 20-50 years. Overall, 181 patients, 70.166 % cases were found positive with H. pylori in serum and 32.6% of cases were positive with H. pylori in stool. Most red blood parameters were significantly decreased in patients compared to control subjects. The numbers of white blood cells and percentage number of neutrophils were increased significantly in positive cases of H. pylori infection. A percentage value of lymphocytes was decreased significantly in positive cases. Results of platelets parameters were decreased in all subjects. In term of type of blood groups, the highest prevalence among individuals with blood group A, B and O. Mean levels of liver and kidney function parameters in the sera were in normal range all patients. In the current study, association of H. pylori infection with smoking, marital status and allergic disease were studied. Over positive cases 70.58 % of these cases were smoking. Upon marital status, H. pylori prevalence was higher in married subjects (65%) as compared to single subjects. And prevalence of non-allergic was higher in negative subjects with H. pylori as compared to positive subjects. Conclusion. H. pylori infection is usually lifelong therefore a positive test, physiological alteration usually denotes active infection unless the patient has received eradication therapy.